Demultiplexação espacial de feixes com vórtices incoerentes - Bezerra, Daniel de Oliveira (2019)
In this dissertation we studied the result of Laguerre-Gauss beam sorter having topological loading using the transformation spiral method for coherent and partially coherent bundles. We observe numerically and experimentally that the use of this spiral provides a robust sorter and good visibility for the determination of the topological charge.